The horizontal prototype of online ordering book system / Zainab Othman, Norfiza Ibrahim and Azida Zainol - Othman, Zainab; Ibrahim, Norfiza; Zainol, Azida (Universiti Teknologi MARA Cawangan Pahang, 2005)
This project aims to create the horizontal prototype to show the functionalities of Online Ordering Book System (OBSYS) using Object Oriented approach. Three main phases are involved in this project. They are: defining requirements, analyzing requirement and validating functionalities. The horizontal prototype of Online Ordering Book System consists of use case diagram, use case specification, class diagram, sequence diagram, collaboration diagram, activity diagram and the list of requirements. This prototype provides a guideline in developing the running system of Online Ordering Book based on the user's perspective.